Tantangan Piutang BPJS dalam Mempertahankan Kestabilan Ekonomi Nasional: Dampak terhadap Keuangan Perusahaan Kecil dan Menengah dan Kelancaran Iuran - Hamdani Hamdani; Fitro Aidil; Ramadhan Adi Nugraha; Rizal Sjarief Sjaiful Nazli (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The National Health Insurance (JKN) program, managed by BPJS Kesehatan, has formed strategic partnerships with micro and small enterprises (MSEs) to support the national healthcare service ecosystem. However, the accumulation of unsettled receivables from BPJS to its MSE partners has created significant challenges to the financial stability of this sector. Based on 2023 data, over 449,000 micro and small businesses were recorded as having outstanding receivables, with a total value exceeding IDR 2 trillion. This study adopts a descriptive quantitative approach to examine the impact of these receivables on the liquidity, solvency, and productivity of MSEs. The findings reveal that although most receivables are classified as “current,” payment delays continue to disrupt cash flow, reduce production capacity, and increase the risk of default. The analysis is grounded in the theoretical frameworks of receivables management, cash flow theory, institutional economics, and the strategic contribution of MSEs to national GDP. The results highlight the urgent need for payment system reform within BPJS, the provision of short-term financial facilities, and the implementation of delay compensation policies to ensure the sustainability of Indonesia’s micro and small enterprise sector.